The Effect of Burnout Management and Work-Life Balance on Quiet Quitting in Hospitals XYZ - Dea Rizka Fathulaela; Alda Firda Nuraulia; Sunimah Sunimah (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to investigate the impact of burnout and work-life balance on quiet quitting within hospital settings. This research utilizes a correlational analytical framework. The independent factors include burnout (X1) and work-life balance (X2), whereas the dependent variable is quiet quitting (Y). The research sample comprised 191 participants, and the data were analyzed via multiple linear regression. The research revealed that burnout and work-life balance collectively influence quiet quitting among hospital personnel. Burnout exhibits a significant amount of 0.001, while work-life balance demonstrates a substantial value of zero. This research model accounts for 57.6% of the diversity in quiet quitting, leaving 42.4% attributable to factors outside the study's scope. Work-life balance exerts a more significant impact on quiet resignation than tiredness. This indicates that the equilibrium between professional and personal life is more critical in mitigating the probability of health workers departing discreetly than the degree of burnout encountered. To prevent quiet termination, hospitals must enhance the well-being of healthcare staff through effective management and promotion of work-life balance.